Taxonomy for software teamwork measurement. Issue 10 (13th January 2014) - Robillard, Pierre N.; Lavallée, Mathieu; Ton‐That, Yvan; Chiocchio, François; Huang, Liguo; Armbrust, Ove
ABSTRACT Despite the fact that software is mostly a team endeavor, the software engineering (SE) literature has not tapped into organizational psychology's conceptual and empirical writings on teams. This paper presents a model of team dynamics adapted to the specificities of SE project teams. The taxonomy is composed of nine episodes that are likely to be found in any software team process. Each episode is described in terms of the input‐process‐output cycle and illustrated with examples. The measurability of the episodes is validated on a capstone student project carried out with an industrial partner. The team activities are recorded by each developer, throughout the project's duration, in the form of work tokens. These work tokens are then associated with episodes by two independent coders. The results show that all the episodes of the proposed taxonomy are measurable, and very few (less than 5% in this field study) remain ambiguous. Most of the ambiguities arise from short episodes that alternate during team process activities. This paper's contribution to software team process research is to synthesize the team literature and draw up a theoretically driven taxonomy of team dynamics specific to SE teams and to provide initial evidence of measurability of the taxonomy. Copyright © 2014 John Wiley & Sons, Ltd.